Oxygen Transport to Tissue XXIX - Kang, Kyung A.; Bruley, Duane F. (Advances in Experimental Medicine and Biology, 2008)
The 34th Annual Conference of the International Society on Oxygen Transport to Tissue (ISOTT) was held during August 12-17, 2006 in Louisville, Kentucky, USA. The emphasis of ISOTT-2006 was on ''Expanding our Horizon. '' In terms of research topics, we added some newer ones - Translational Studies, Tissue Engineering, and Nanobiotechnology. In terms of participants, we put extra effort into including more junior researchers because we felt that they were the future of our society and for the first time in ISOTT history we had presentations made by high school students. In terms of organization, it was truly local, national, and international. The support in organizing ISOTT-2006 came from various directions: We would like to express our special thanks to the University of Louisville (UofL), especially to the UofL Provost Office, Speed School of Engineering, School of Medicine, and the office of the Vice President of Research. UofL's financial support allowed us to supplement the student's registration fees s- stantially and to invite so many excellent distinguished lecturers. It should be noted that none of our invited speakers requested an honorarium - we thank them immensely. I would personally like to thank the Chemical Engineering Department of UofL for allowing me to take time off from my teaching resp- sibility. We appreciate UofL President Ramsey's visit to our dinner held at the Derby Museum. We thank the Case Western Reserve University for having their MIMS Center symposium with us.